Correlation of Headache Frequency and Psychosocial Impairment in Migraine: A Cross‐Sectional Study. Issue 5 (23rd August 2013) - Ruscheweyh, Ruth; Müller, Melanie; Blum, Bernhard; Straube, Andreas
<x xml:space="preserve">Abstract</x> Objective To investigate if a headache frequency of 15 days per month constitutes a turning point in the psychosocial impairment associated with migraine. Background Migraine is differentiated into episodic and chronic forms based on a headache frequency criterion (< vs ≥15 headache days per month). It is presently not clear if this criterion represents a clinically and pathophysiologically meaningful turning point of the disease. Methods Six hundred and one migraine patients completed measures of pain‐specific disability (Migraine Disability Assessment Scale, von Korff scale), health‐related quality of life (Short Form‐12 Health Survey), habitual well‐being (Marburg questionnaire), and anxiety and depression (Hospital Anxiety and Depression Score). Results A significant increase of psychosocial impairment with the number of headache days per month was found at lower headache frequencies, but leveled off at higher headache frequencies. Visual inspection and spline interpolation suggested that the turning point was not exactly at 15 headache days per month but rather around 13.3 (confidence interval: 8.9‐17.7) days. Accordingly, significant correlations between headache days and psychosocial impairment were found in the group with ≤13 headache days per month (Spearman's rho = 0.25, P < .001) but not in the group with >13 headache days (rho = −0.02, n.s.). Conclusion These results suggest that a meaningful turning point in psychosocial impairment associated with migraine is located around 13.3 headache days per month, somewhat below the 15‐headache days criterion that by definition separates chronic from episodic migraine. However, confidence intervals surrounding the turning point were large. Further studies will be needed to more exactly localize the turning point.